Epidemiology and outcome of severe sepsis and septic shock in intensive care units in mainland China. - Jianfang Zhou; Chuanyun Qian; Mingyan Zhao; Xiangyou Yu; Yan Kang; Xiaochun Ma; Yuhang Ai; Yuan Xu; Dexin Liu; Youzhong An; Dawei Wu; Renhua Sun; et al. (PLoS ONE, 2014)
INTRODUCTION: Information about sepsis in mainland China remains scarce and incomplete. The purpose of this study was to describe the epidemiology and outcome of severe sepsis and septic shock in mixed ICU in mainland China, as well as the independent predictors of mortality. METHODS: We performed a 2-month prospective, observational cohort study in 22 closed multi-disciplinary intensive care units (ICUs). All admissions into those ICUs during the study period were screened and patients with severe sepsis or septic shock were included. RESULTS: A total of 484 patients, 37.3 per 100 ICU admissions were diagnosed with severe sepsis (n = 365) or septic shock (n = 119) according to clinical criteria and included into this study. The most frequent sites of infection were the lung and abdomen. The overall ICU and hospital mortality rates were 28.7% (n = 139) and 33.5% (n = 162), respectively. In multivariate analyses, APACHE II score (odds ratio[OR], 1.068; 95% confidential interval[CI], 1.027-1.109), presence of ARDS (OR, 2.676; 95%CI, 1.691-4.235), bloodstream infection (OR, 2.520; 95%CI, 1.142-5.564) and comorbidity of cancer (OR, 2.246; 95%CI, 1.141-4.420) were significantly associated with mortality. CONCLUSIONS: Our results indicated that severe sepsis and septic shock were common complications in ICU patients and with high mortality in China, and can be of help to know more about severe sepsis and septic shock in China and to improve characterization and risk stratification in these patients.